Hexafluoropropylene oxide-dimer acid (HFPO-DA or GenX) alters maternal and fetal glucose and lipid metabolism and produces neonatal mortality, low birthweight, and hepatomegaly in the Sprague-Dawley rat. (January 2021) - Conley, Justin M.; Lambright, Christy S.; Evans, Nicola; McCord, James; Strynar, Mark J.; Hill, Donna; Medlock-Kakaley, Elizabeth; Wilson, Vickie S.; Gray, L. Earl
Graphical abstract: Highlights: HFPO-DA (or GenX) is a developmental toxicant in the rat. Dysregulation of carbohydrate and lipid metabolism are critical key events. PPAR (alpha and gamma) signaling pathways highly involved in metabolic effects. Maternal thyroid hormone concentrations also significantly reduced. GenX produces neonatal mortality at similar serum concentration to PFOS. Abstract: Hexafluoropropylene oxide dimer acid (HFPO-DA or GenX) is an industrial replacement for the straight-chain perfluoroalkyl substance (PFAS), perfluorooctanoic acid (PFOA). Previously we reported maternal, fetal, and postnatal effects from gestation day (GD) 14-18 oral dosing in Sprague-Dawley rats. Here, we further evaluated the perinatal toxicity of HFPO-DA by orally dosing rat dams with 1–125 mg/kg/d (n = 4 litters per dose) from GD17-21 and with 10–250 mg/kg/d (n = 5) from GD8 – postnatal day (PND) 2. Effects of GD17-21 dosing were similar to those previously reported for GD14-18 dosing and included increased maternal liver weight, altered maternal serum lipid and thyroid hormone concentrations, and altered expression of peroxisome proliferator-activated receptor (PPAR) pathway genes in maternal and fetal livers. Dosing from GD8-PND2 produced similar effects as well as dose-responsive decreased pup birth weight (≥30 mg/kg), increased neonatal mortality (≥62.5 mg/kg), and increased pup liver weight (≥10 mg/kg). Histopathological evaluation of newborn pup livers indicated a marked reduction in glycogen stores and pups were hypoglycemic at birth. Quantitative gene expression analyses of F1 livers revealed significant alterations in genes related to glucose metabolism at birth and on GD21. Maternal serum and liver HFPO-DA concentrations were similar between dosing intervals, indicating rapid clearance, however dams dosed GD8 – PND2 had greater liver weight and gestational weight gain effects at lower doses than GD17-21 dosing, indicating the importance of exposure duration. Comparison of neonatal mortality dose–response curves between HFPO-DA and previously published perfluorooctane sulfonate (PFOS) data indicated that, based on serum concentration, the potency of these two PFAS are similar in the rat. Overall, HFPO-DA is a developmental toxicant in the rat and the spectrum of adverse effects is consistent with prior PFAS toxicity evaluations, such as PFOS and PFOA.